Differential lipid signaling from CD4+ and CD8+ T cells contributes to type 1 diabetes development - White, Tayleur D.; Almutairi, Abdulaziz; Gai-Tusing, Ying; Stephenson, Daniel J.; Stephenson, Benjamin D.; Chalfant, Charles E.; Lei, Xiaoyong; Lu, Brian; Hammock, Bruce D.; DiLorenzo, Teresa P.; Ramanadham, Sasanka (Frontiers in Immunology, 2024)
We reported that Ca2+-independent phospholipase A2β (iPLA2)-derived lipids (iDLs) contribute to T1D onset. As CD4+ and CD8+ T-cells are critical in promoting -cell death, we tested the hypothesis that iDL signaling from these cells participate in T1D development. To address this, CD4+ and CD8+ T-cells from wild type non-obese diabetic (NOD) and NOD.iPLA2+/- (NOD.HET) mice were administered in different combinations to immunodeficient NOD.scid. In mice receiving only NOD T-cells, T1D onset was rapid (5 weeks), incidence 100% by 20 weeks, and islets absent. In contrast, onset was delayed 1 week and incidence reduced 40-50% in mice receiving combinations that included NOD.HET T-cells. Consistently, islets from these non-diabetic mice were devoid of infiltrate and contained insulin-positive -cells. Reduced iPLA2 led to decreased production of proinflammatory lipids from CD4+ T-cells including, prostaglandins and dihydroxyeicosatrienoic acids (DHETs), products of soluble epoxide hydrolase (sEH); and inhibition of their signaling decreased (by 82%) IFN+CD4+ cells abundance. However, only DHETs production was reduced from CD8+ T-cells and was accompanied by decreases in sEH and granzyme B. These findings suggest that differential select iDL signaling in CD4+ and CD8+ T-cells contributes to T1D development, and that therapeutics targeting such signaling might be considered to counter T1D.